2022
DOI: 10.1172/jci.insight.159578
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3 like 1 contributes to the development of pulmonary vascular remodeling in pulmonary hypertension

Abstract: Chitinase 3-like 1 (CHI3L1) is the prototypic chitinase-like protein mediating inflammation, cell proliferation, and tissue remodeling. Limited data suggests CHI3L1 is elevated in human pulmonary arterial hypertension (PAH) and is associated with disease severity. Despite its importance as a regulator of injury/repair responses, the relationship between CHI3L1 and pulmonary vascular remodeling is not well understood. We hypothesize that CHI3L1 and its signaling pathways contribute to the vascular remodeling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…YKL-40 is a circulating inflammatory factor detected in macrophages, smooth muscle cells, fibroblasts, and astrocytes (Yeo et al, 2019). Several studies have reported that YKL-40-mediated inflammatory remodelling is widely present in the cardiovascular and respiratory systems and may be a predictor of remodelling (Furukawa et al, 2019;Sun X. N. et al, 2022). In this study, YKL-40 levels were significantly higher in patients with positive intracranial arterial remodelling than in those without positive remodelling, possibly because YKL-40 acts as a pro-inflammatory signal to endothelial cells, regulates macrophage activation (Batinic et al, 2012), activates the protein kinase pathway, increases protease production, disrupts the internal elastic layer and collagen matrix, and causes positive intracranial arterial remodelling (He et al, 2013;Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…YKL-40 is a circulating inflammatory factor detected in macrophages, smooth muscle cells, fibroblasts, and astrocytes (Yeo et al, 2019). Several studies have reported that YKL-40-mediated inflammatory remodelling is widely present in the cardiovascular and respiratory systems and may be a predictor of remodelling (Furukawa et al, 2019;Sun X. N. et al, 2022). In this study, YKL-40 levels were significantly higher in patients with positive intracranial arterial remodelling than in those without positive remodelling, possibly because YKL-40 acts as a pro-inflammatory signal to endothelial cells, regulates macrophage activation (Batinic et al, 2012), activates the protein kinase pathway, increases protease production, disrupts the internal elastic layer and collagen matrix, and causes positive intracranial arterial remodelling (He et al, 2013;Xu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its pathophysiologic role in embolus formation rather than in the atherosclerosis development, elevated plasma YKL-40 concentrations bear a 2-fold increased risk of ischemic stroke and venous thromboembolism, but not myocardial infarction (MI) ( 18 ). This finding could be explained with the involvement of YKL-40 in certain biological processes: smooth muscle cell proliferation, inhibition of pulmonary vascular endothelial cell apoptosis, inducing the loss of the endothelial barrier function, and endothelial-mesenchymal transition ( 24 ). In Asian population certain SNPs in CHI3L1 gene ( e.g .…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…In summary, YKL-40 concentrations seem to be closely intertwined with immune mediated, infective or mechanically induced ED, thus providing a valuable research objective for early identification and improved stratification of patients in disease states etiologically associated with ED ( e.g. CKD and CAD) ( 24 , 91 , 94 , 95 ). In transplanted deceased donor kidneys with AKI, increased urinary concentrations and more prominent YKL-40 expression in kidneys were associated with preferable kidney transplant recipient outcome, most likely as a part of YKL-40 upregulation in physiological response to prevent oxidative damage and activate renal repair mechanisms ( 15 , 95 ).…”
Section: Urinary Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The chitinase-like protein family is a glycoprotein similar to chitinase, a plant hydrolase that catalyzes the breakdown of chitin to protect the host against various pathogens and lacks enzymatic activity [10,11]. They are emerging as biomarkers for a wide range of neurological disorders, but their physiological role remains unclear [12].…”
Section: Introductionmentioning
confidence: 99%